Information Communication Technology Utilisation for Serial and Bibliographic Routines in Federal University Libraries in North East, Nigeria - Vandi, Ibrahim; Agboola, Bukola; Manja, Mary (NIU Journal of Educational Research; Vol 12 No 2 (2026): NIU Journal of Educational Research, Vol. 12, No. 2, June 2026, 2026)
The study examined Information Communication Technology Utilisation for Serial and Bibliographic Routines in Federal University Libraries in North- East, Nigeria. The study was guided by three objectives, three research questions and two null hypotheses. The study adopted descriptive survey research design. Three hundred and ninety-six (399) librarians and paraprofessional librarians from the six federal university libraries in northeastern Nigeria made up the study's population.  Using the census sampling technique, the study's sample size is 399. A questionnaire was employed as the research instrument of this study. Tagged, “Information Communication Technology Utilisation for Serial and Bibliographic Routines Questionnaire” (ICTSBRQ). The questionnaire was based on a four-point rating scale. The instrument was face validated. Two research questions were answered using Pearson Product Moment Correlation Coefficient. The two null hypotheses were also tested using Pearson Product Moment Correlation Coefficient at .05 level of significance. Based on the findings, it was concluded that there is relationship between ICT utilisation for serial and bibliographic routines in federal university libraries in North East, Nigeria. It was recommended that appropriate ICT facilities should be provided by the management of the libraries under study for easier and successful serial and bibliographic routines. Librarians should also have positive attitude towards ICT utilisation for effective serial and bibliographic routines in federal university libraries in North East, Nigeria. Keywords: Information Communication Technology, ICT utilization, effective serial and bibliographic routines, federal university libraries, North East, Nigeria.